ANALISIS AKUNTANSI DAN PELAPORAN BANTUAN SOSIAL DAN HIBAH - , Sriyani (JURNAL INFO ARTHA, 2016)
This study aims to determine the accounting and reporting of social aid and grants using literature study, specifically analyzing the existing rules to determine how the accounting and reporting practices of social aid and grants can be applied to the central government and local governments. The absence of guidelines which provide definitions and accounting treatment of social aid expenditure is another problem. Based on Technical Bulletin No. 13 about Grant, there are problems related to management patterns of grants acceptance conducted by the state ministries/agencies and local governments.Accrual-based accounting in the social aid transaction consists of social aid expense and  expenditure. The accountability of accounting for the transaction consists of the recognition,  measurement, presentation and disclosure. Grants can be categorized into grant revenue and grant expenditure/expense. Grant is written in the grant agreement between the grantor and grantee with no compensation or direct repayment. Grant consists of arranged grants and direct grants, whereas grant expenditure should be planned. The arranged grant expenditures are included in the state budget or the General Budget Policy and Provisional Budget Priorities and Funding Levels-Local Government Budget. Implementation of the accrual-based grant as an expense in the Statement of Operations and expenditure in the Budget Realization Report.